A scheduling model for a knitting planning problem - Pimentel, Carina (2012)
In this paper we present two planning and scheduling models for a real problem of a textile industry that produces fine knitted goods. In both of them we develop plans to assist the knitting planning of one of three knitting subsections. In this problem we intend to assign and sequence, within a set of available and identical parallel machines, the demand associated with each component or garment part. This demand can be split in lots of smaller quantities and these lots can be independently produced at any time in one or more of the available machines. In the first model we develop a mixed integer programming (MIP) formulation and in the second one we develop network flow based models and a scheduling heuristic. The main advantage of the second model, in opposition to the first one, is the small computational resources needed to solve this huge and complex problem. We solve an instance generated in accordance with the characteristics of the real problem by the second model and present some performance measures.